Rare-Earth Nanomaterials For Bio-Probe Applications (Applied Biological Research, 2017)
Rare-earth compounds are of immense significance due to the presence of f-orbital electrons and the resultant magnetic, electronic, catalytic,  chemical and optical qualities. This leads to their practical application  in diverse fields, such as luminescent devices or phosphors (component  in LEDs, household compact fluorescent lamps, high-resolution flat  panel displays), medical diagnostics and imaging, biochemical probes,  powerful magnets, sensors, and in the catalysis of some technically  important chemical processes. However, much attention has recently  been devoted to the synthesis of rare-earth-based compounds in  nanometric dimensions that can perform multiple functions, such as  fluorescence imaging, drug delivery, and so on. In this mini review, a  short summary of the applications of rare-earth nanomaterials in the  fluorescent labelling of cells, MRI contrast imaging, and dual imaging  modalities have been discussed.
Keywords: Fluorescent labelling; MRI imaging; nanomaterials; rare-earths